MEL-IRIS: An Online Tool for Audio Analysis and Music Indexing - Dimitrios Margounakis; Dionysios Politis; Konstantinos Mokos (International Journal of Digital Multimedia Broadcasting)
Chroma is an important attribute of music and sound, although it has not yet been adequately defined in literature. As such, it can be used for further analysis of sound, resulting in interesting colorful representations that can be used in many tasks: indexing, classification, and retrieval. Especially in Music Information Retrieval (MIR), the visualization of the chromatic analysis can be used for comparison, pattern recognition, melodic sequence prediction, and color-based searching. MEL-IRIS is the tool which has been developed in order to analyze audio files and characterize music based on chroma. The tool implements specially designed algorithms and a unique way of visualization of the results. The tool is network-oriented and can be installed in audio servers, in order to manipulate large music collections. Several samples from world music have been tested and processed, in order to demonstrate the possible uses of such an analysis.